Biofortification: an approach to eradicate micronutrient deficiency - Avnee,; Sood, Sonia; Chaudhary, Desh Raj; Jhorar, Pooja; Rana, Ranbir Singh (Frontiers in Nutrition, 2023)
Micronutrient deficiency also known as "hidden hunger" refers to a condition that occurs when the body lacks essential vitamins and minerals that are required in small amounts for proper growth, development and overall health. These deficiencies are particularly common in developing countries, where a lack of access to a varied and nutritious diet makes it difficult for people to get the micronutrients they need. Micronutrient supplementation has been a topic of interest, especially during the Covid-19 pandemic, due to its potential role in supporting immune function and overall health. Iron (Fe), zinc (Zn), iodine (I) and selenium (Se) deficiency in humans are significant food-related issues worldwide. Biofortification is a sustainable strategy that has been developed to address micronutrient deficiencies by increasing the levels of essential vitamins and minerals in staple crops that are widely consumed by people in affected communities. There are a number of agricultural techniques for biofortification, including selective breeding of crops to have higher levels of specific nutrients, agronomic approach using fertilizers and other inputs to increase nutrient uptake by crops and transgenic approach. The agronomic approach offers a temporary but speedy solution while the genetic approach (breeding and transgenic) is the long-term solution but requires time to develop a nutrient-rich variety.